Repeatability of Corneal Deformation Response Parameters by Dynamic Ultra High-speed Scheimpflug Imaging in Normal and Keratoconus Eyes. Issue 1 (January 2022) - Henriquez, Maria A.; Gomez, Isabel; Camino-Quezada, Maythe; Izquierdo, Luis; Chauca, José; Binder, Perry S.
Abstract : Purpose: To assess the repeatability of corneal dynamic response (CDR) parameters in normal and keratoconus (KC) eyes using ultra high-speed Scheimpflug imaging. Methods: Prospective, comparative, observational study, including eyes of 112 patients that underwent high-speed Scheimpflug imaging analysis (Corvis ST, OCULUS). Twenty-one CDR parameters were evaluated to asses repeatability using: coefficient of repeatability (CR), coefficient of variation, intraclass correlation coefficient (ICC) and within-subject SD. Three consecutive measurements by the same operator were performed for each eye. Results: There were no significant differences between the three consecutive measurements for all parameters in both normal and KC eyes. 71.42% (15 of the 21 parameters evaluated) and 85.71% (18 of the 21 parameters) were highly repeatable in the normal and KC group, respectively. The tomographic biomechanical index (TBI), corneal biomechanical index (CBI), and stiffness parameter (SPA1) showed an ICC of 0.978, 0.954, and 0.958 in normal and 0.982, 0.892, and 0.978 in KC eyes, respectively. The CR in normal eyes for TBI, CBI, and SPA1 were 0.169, 0.242, and 14.12, respectively, and for KC eyes 0.06, 0.23, and 13.64, respectively. Conclusions: Most of the corneal dynamic response parameters were highly repeatable in normal and KC eyes.